Using portfolio in teaching reading skill to second-year non English major student at University of Economics and Business- Vietnam National University - Nguyễn, Quỳnh Hoa (University of Languages and International Studies, 2017)
In the worls, various kinds of portfolio have been used since the early of 1990s in teaching foreign languages and have shown promising results. In Vietnam, portfolio has gradually become a favourable teaching tool at many universities as it combines both instruction and assessment. Moreover, portfolio focuses on various language and learning skills not just concrete language items.